The Alzheimer's disease metabolic brain pattern in mild cognitive impairment. Issue 12 (December 2017) - Meles, Sanne K; Pagani, Marco; Arnaldi, Dario; De Carli, Fabrizio; Dessi, Barbara; Morbelli, Silvia; Sambuceti, Gianmario; Jonsson, Cathrine; Leenders, Klaus L; Nobili, Flavio
We investigated the expression of the Alzheimer's disease-related metabolic brain pattern (ADRP) in 18 F-FDG-PET scans of 44 controls, 27 patients with mild cognitive impairment (MCI) who did not convert to Alzheimer's disease (AD) after five or more years of clinical follow-up, 95 MCI patients who did develop AD dementia on clinical follow-up, and 55 patients with mild-to-moderate AD. The ADRP showed good sensitivity (84%) and specificity (86%) for MCI-converters when compared to controls, but limited specificity when compared to MCI non-converters (66%). Assessment of 18 F-FDG-PET scans on a case-by-case basis using the ADRP may be useful for quantifying disease progression.